Children’s point of view to health related social factors - Jūratė Grubliauskienė; Rita Vaičekauskaitė (Social Welfare: Interdisciplinary Approach)
The article rise a problem that we pay not sufficient attention to children’s point of view to health. Children’s health understanding is close related with the absence of disease. Due to the growing age and educational programs children’s percpetion about health is extended to social factors. However, it is constant challenge to to find out meaningfull correlations of social factors with health as it is braod field, influenced by plenty of aspects. The article introduce original results of KIDSCREEN 52 survey which is conducted for the first time in Lithuania. Children’s point of view to health related social factors are conjunct with health status, communication with parents, age and gender. Children without health problems demonstrate positive evaluation to health related social factors. The more children talk with parents about health the more they demonstrate positive evaluation to health related social factors. The boys revealed that they more often than girls are talking to their parents about health in general, they assess their health better and they are very likely to agree with statements describing their physical health and well-being. The age of the children interact with all factors of the questionnaire in a weak but statistically significant correlation. A direct correlation was found between children's age and overall health assessment. All aforementioned statements are based on statistically significant correlations, which are demonstrated later in the article. Our research findings are consistent with already existing; therefore, they compliment meaningfully the social ecological approach to health promotion and education.